UPAYA MEWUJUDKAN "STUDENT WELL BEING" MELALUI PENINGKATAN KOMPETENSI GURU DALAM MENERAPKAN PEMBELAJARAN BERDEFRENSIASI DI SMA NEGERI 1 TALUN KABUPATEN BLITAR - Sasmito, Edy (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
The realization of "Student Well Being" in schools is one of the important programs in an effort to improve education services during the recovery period of the education world after our country was hit by a pandemic. Various efforts have been made by the government, such as the implementation of the Independent Learning Curriculum as stated in the Decree of the Ministry of Education and Culture No. 56 of 2022. This research was conducted on teachers of SMA Negeri 1 Talun in order to improve their professional competence. The method used in this study is the School Action Research (PTS) method. This research is divided into three cycles. Based on the results of data analysis in cycle 1, teacher competence on differentiation learning increased from pre-cycle. It is evident from the results of the pre-test which averaged 5.8 and the post-test increased to 8.8 with an average increase of 2.95% in value. Teacher competence is also proven in the application of field supervision in cycle 2 even though it is still not fully said to be successful because of the 64 teachers as research subjects, there are 38 people or about 59% who still have not implemented differentiated learning well. After the improvement and strengthening of teachers, only in cycle 3 the research can be said to be successful because there are 53 teachers or about 83% successful, while there are 4 teachers whose competence in implementing differentiated learning is very good if the percentage is around 6%, the remaining 7 teachers or about 11% which shows poor competence. From the results of observations of the level of well being shown by students in differentiated learning, it was found that there were 35 teaching teachers or about 55% whose students in the class could show very good Well Being. Meanwhile, there are 22 teaching teachers (34%) whose students can show quite well being during the teaching and learning process. Furthermore, there are 7 teachers (11%) who when teaching in class their students are not good at showing their well being. Thus the results of this study can be used as a positive recommendation for the realization of Student well Being in schools as in the contents of the Independent Learning Curriculum.